ANDREJA ŽELE, MIRA KRAJNC IVIČ, 2020: SODOBNA SLOVENSKA SKLADNJA: DISKURZNI IN SLOVNIČNI VIDIK: Maribor: Univerzitetna založba Univerze. (Mednarodna knjižna zbirka Zora, 134). 460 str. - Žele, Andreja; Krajnc Ivič, Mira (Slavia Centralis, 2020)
The authors of the article present a linguistic research entitled Sodobna slovenska skladnja: diskurzivni in slovnični vidik (Contemporary Slovene Syntax: Discursive and Grammatical Aspects), the starting point of which is the text as a communicative and grammatical unit and at the same time a whole.